Characterization of Ethanol Extract from Agarwood (Aquilaria microcarpa Baill.) Leaf - Rahmanto, Beny; Halwany, Wawan; Lestari, Fajar; Anwar, Khoerul; Triyasmono, Liling; Rizki, Muhammad Ikhwan; Turjaman, Maman (Tropical Biopharmaca Research Center, IPB University, 2018)
The aim of this research is to determine the specific and non-specific parameter from ethanolic extract of A. microcarpa. Specific parameters such as the organoleptic properties, content of water and ethanol soluble compound, and chhromatogram profile of the extract. In contrast, the non-specific parameter includes drying losses, ash levels, microbiological contamination levels, and heavy metal contamination levels. The results showed that the organoleptic properties of ethanolic extract of A. microcarpa was thick, blackish brown color, bitter taste and have distinctive odor. The average content of water-soluble compounds of 66.93%, ethanol-soluble of 47.97%, and chromatogram profile with Rf 0.636. The non-specific parameters results were drying losses of 5.50%, total ash content of 3.73%, acid-insoluble ash of 2.13%, microbial contamination testing results of 1.2x102-5.5x103 colonies/g, and total mold/ yeast contaminants of 10-100 colonies/g. Heavy metal contamination Pb levels and Cd levels were 5.47 mg/kg and 0.19 mg/kg respectively. These studies suggested that the observed specific and non-specific parameters may be helpful for establishing pharmacopoeia standards of A. microcarpa and to ensure uniformity of extract effect.